2021
DOI: 10.1002/jso.26513
|View full text |Cite
|
Sign up to set email alerts
|

FDG‐PET for preoperative evaluation of tumor invasion in ampullary cancer: A retrospective analysis

Abstract: Background: Tumor invasion is the most significant prognostic factor in ampullary cancer and is thus a crucial factor in decision making for treatment. Endoscopic ultrasound can be performed to evaluate tumor invasion, but its diagnostic accuracy varies depending on the endoscopist. This study aimed to assess the usefulness of fluorodeoxyglucose positron emission tomography (FDG-PET) for preoperatively predicting tumor invasion in ampullary cancer. Methods:We retrospectively evaluated 44 patients with ampullar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…2-[ 18 F]FDG PET/CT, a noninvasive tool for staging cancers with upregulated glucose metabolism, is widely used [ 17 18 19 24 34 ]. Watanabe et al [ 25 ] highlighted the link between tumor SUVmax, tumor invasion extent, and nodal metastasis, potentially guiding the choice of EP over surgery in tumors with a low SUVmax. Consistent with this, our study noted that an SUVe ≥ 1.7 and PET-detected nodal disease are probable indicators of ampullary cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2-[ 18 F]FDG PET/CT, a noninvasive tool for staging cancers with upregulated glucose metabolism, is widely used [ 17 18 19 24 34 ]. Watanabe et al [ 25 ] highlighted the link between tumor SUVmax, tumor invasion extent, and nodal metastasis, potentially guiding the choice of EP over surgery in tumors with a low SUVmax. Consistent with this, our study noted that an SUVe ≥ 1.7 and PET-detected nodal disease are probable indicators of ampullary cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These immunohistopathologic characteristics are also frequently seen in ampullary cancer [ 1 20 21 22 ]. Previous studies reported that 2-[ 18 F]FDG PET/CT can help evaluate tumor invasion and predict survival in ampullary cancer [ 23 24 25 ]. In this study, we aimed to investigate whether 2-[ 18 F]FDG PET/CT could help evaluate the risk of malignancy in endoscopy-detected ampullary tumors.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Patients with AAC tend to present typical symptoms of biliary obstruction at relatively early stages, but these symptoms are mostly non-specific and are therefore often detected incidentally during examinations. 8 , 9 Although the early detection of symptoms helps to improve the resection rates in radical surgery, which is the standard treatment for AAC, high risks of recurrence, and postoperative mortality are major concerns. 10 , 11 Different centers have reported a wide range of 5-year overall survival (OS) rates after AAC resection of 32%–69.1%, with a median survival time of 28–70 months, while the 10-year OS rate ranged from 26% to 48%.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has used various types of prediction models to assess the short-term survival rates of AAC, including Kaplan–Meier survival analysis, logistic regression, and the Cox proportional hazards (CoxPH) model. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 Kaplan–Meier survival analysis is the most commonly method used to investigate the prognostic factors for AAC, which does not allow adjustments for confounders and has a restrictive assumption of non-informative censoring. 24 , 25 Logistic regression models aim to estimate the relationship between potential factors and survival outcomes as well as adjust for confounders.…”
Section: Introductionmentioning
confidence: 99%